Perancangan Animasi Game Interaktif Puzzle Hewan Untuk Anak Anak Menggunakan Adobe Flash CS6 - Harahap, Syaiful Zuhri; Sitompul, Muhammad Sofyan; Irmayani, Deci (Journal of Computer Science and Information System(JCoInS), 2022)
Games in this world contain various types that represent puzzle games, one of the forms of the game that requires accuracy, trains us to concentrate the mind, must collect in compiling the pieces of the puzzle image into pictures that are made and equipped that have educational value. This animal puzzle game is made to introduce animals that are often seen both on television and in pictures or stories to provide knowledge to children.